Software engineering education in cooperation with industrial partners - Horváth, Zoltán; Kozsik, Tamás; Lövei, László (Teaching Mathematics and Computer Science, 2010)
This paper presents our experiences on teaching software engineering in teams which are organized around different R+D projects. These long-running, innovative projects are carried out in cooperation with industrial partners, and are supported by student exchange. While MSc and PhD students work together with faculty staff members on the projects in an industrial-like environment, the students develop skills that would be otherwise very hard for them to obtain. The methodological contributions of the paper are illustrated by, and substantiated with, the description of a concrete software engineering project.